An Analysis of Airbnb Host-Guest Relationships: A Qualitative Study of Relationship Development and Outcomes - Nusantara, Aji Cahya (Curtin University, 2023)
Host-guest relationships have become one of the most discussed topics in the context of Airbnb in recent years. An extensive literature review revealed that research into this domain has yet to adequately map the relationship development process and outcomes between guests and hosts. Thus, this study addresses these gaps by conducting a one-sequence study of the Airbnb guest journey to determine when and how transactionally focused Airbnb stays progress to the formation of friendships between guests and hosts. Its findings contribute to the extant literature by providing clarity regarding the possibility of friendship development in an Airbnb context, as well as in the broader domain of tourism and hospitality.